THE EFFECT OF SOCIAL MEDIA ADDICTION ON MARRIAGE ROLE EXPECTATIONS - Hafize Dağ Tüzmen; Büşra Duran; Şerife İrem Döner (Hemşirelikte Araştırma Geliştirme Derneği, 2023)
Aim: The aim of this study was to determine the effect of social media on the platform usage status of married social individuals and their marriage thoughts/expectations. Material and Methods: One unit difference, 95% power, α = 0.05 margin of error was calculated with the G Power 3.1 program, which included 400 married individuals between the ages of 15-49, who came from here and were structured in a relationship-seeking type. Data were collected using the introductory information formula, Social Media Addiction Scale - Adult Form and Marriage Role Expectations Scale. SPSS 25 program was used in the analysis and evaluation of the data. t-test for evaluating normally distributed data, One-Way Analysis of Variance; Kruskall Wallis, Mann Whitney-U used. Statistical consumption level was accepted as p